YUGOSLAV TOURISTS IN THE CZECHOSLOVAK SPAS DURING THE INTERWAR PERIOD (1918-1939) - Milan Balaban; Irena Balaban Cakirpaloglu; Dalibor Savić (Istorija 20. Veka)
This study explores the overlooked phenomenon of Yugoslav tourists in Czechoslovak spas during the interwar period, employing archival research, travelogues, and contemporary periodicals. The tourist exchange, driven by rich economic relations, reveals a dynamic interplay of socio-cultural interactions. Focused on spas like Karlovy Vary, Mariánské Lázně, Poděbrady, and others, the research uncovers the experiences of Yugoslav elites in these transnational spaces, contributing to a broader understanding of interwar tourism and diplomatic ties in Central Europe.